Seismic isolation of viaduct piers by means of a rocking mechanism. - Chen, Yi-Hsuan (Earthquake engineering & structural dynamics.)
Rocking mechanism can be an effective means of seismic isolation, despite the fact that it is rarely conceived a possible alternative. In this study, the feasibility of utilizing a rocking mechanism for earthquake protection of slender viaduct pier structures is explored both analytically and experimentally. With a discontinuous interface between the pier footings and the underlying pile caps, a rocking system is designed to rock intermittently as the seismic overturning moment exceeds the restoring moment provided by gravity. During the rock mode, the resisting flexural moment in the pier is released while the earthquake load is counteracted by the rotational inertia with respect to the supporting foot, thus preventing the columns from yielding. Analytical modelling of this non-linear dynamic system is derived with a numerical procedure developed based on the fourth-order Runge?Kutta?Nyström method. A series of tests including the free rocking and seismic performance test, has been conducted using a 1:50 scaled-down model structure of a typical viaduct pier system. Both analytical and experimental results show that the rocking pier system (RPS) for seismic protection of viaduct pier structures is effective and stable, and the stronger the earthquake intensity the more pronounced the control efficiency. The concept of using rocking mechanism for seismic isolation of viaduct pier structures has been demonstrated feasible and promising. Nevertheless, practical issues such as prevention of overturning, foot damage due to impact, or possible sliding of the pier following impact need to be carefully dealt with in the design aspect.